Design and Development of an IoT-based Pulmonary Function Monitoring Device of FVC and FEV1 for Children with Bronchial Asthma - Luthfiyah, Sari (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
Health information technology plays a crucial role in managing the healthcare of patients and their families during illness. One of the frequently encountered diseases is Asthma, a chronic inflammatory disorder of the respiratory tract that is reversible and fluctuating, capable of causing exacerbations with mild to severe symptoms and even death. The objective of this research is to develop a device to facilitate the monitoring and input of data regarding pulmonary volume measurements (spirometry). The sensors used for measuring pulmonary volume are the flow turbine sensor, while the SpO2 sensor used is the MAX30102. The data obtained from the sensor measurements will be processed on the ESP32. A health monitoring application is created using Kodular software, which incorporates a MySQL database for data storage. Furthermore, the examination results can be accessed through an Android application on a tablet or smartphone. The results obtained from this research indicate an error value of 8.78% for FVC, 14% for FEV1, and a FEV1/FVC ratio of 4.6%, with zero data loss. It is expected that the spirometer with Internet of Things (IoT) capabilities will be implemented, as monitoring can be easily conducted anywhere. The portable design will facilitate future examinations. The implications of this study are that it obtains information about individual variability in lung function measurement, the public can better understand the importance of respiratory health monitoring, as well as support the development of better medical technology to improve lung disease diagnosis and management and improve spirometer technology.